A Delphi process to build consensus on revised Emergency Obstetric and Newborn Care (EmONC) signal functions and levels of care - Sarah G. Moxon; Alexandra Wharton-Smith; Sudha Sharma; Jalemba Aluvaala; Oona M. R. Campbell; Gagan Gupta; Samantha Lobis; Caitlin Warthin; Loveday Penn-Kekana; Lynn P. Freedman (PLoS ONE, 2025)
The emergency obstetric care (EmOC) monitoring framework has been used for decades to monitor the availability and use of EmOC services in low- and middle-income countries (LMICs). EmOC monitoring is based around eight signal functions, a shortlist of key clinical interventions capable of averting deaths from the main direct causes of maternal mortality, categorised between two levels of care: basic and comprehensive, with a newborn resuscitation signal function added in 2009. The Re-Visioning Emergency Obstetric and Newborn Care (EmONC) Project (2020–2024) aimed to update the EmOC approach to reflect new knowledge in maternal and newborn health (MNH), and to expand the scope of the original EmOC monitoring framework. The project used technical workstreams and workshops to arrive at new proposals. This paper reports on the approach used to build consensus on a revised set of EmONC signal functions and levels of care. Using a three-round online Delphi approach, consensus (≥85%) was sought from a diverse panel of global MNH experts on EmONC signal functions and their placement at different levels of care, based on existing evidence-based guidelines. The process was iterative, each round building on the previous, and embedded in the wider Re-Visioning EmONC project; the output from each round involved coordination of inputs from multiple tiers of technical experts, including UN agencies, via technical expert groups, workstreams and workshops. The Delphi study recruited 113 experts in MNH from a range of geographic and economic settings, specialities and professions, including clinical, academic and programme expertise. The output from the three rounds included substantial convergence, resulting in set of 25 signal functions (11 obstetric, 13 neonatal and 1 referral) that reflect the spectrum of EmONC required for women and newborns. The revised EmONC signal functions are intended as a simple approach to allow health system managers to visualise their EmONC services, and as a means to hold health systems accountable to provide the main interventions to avert preventable maternal and newborn morbidity and mortality, and stillbirths.